Mobility of People and Goods across the Border of West Kalimantan and Sarawak - Fariastuti Fariastuti (Antropologi Indonesia, 2002)
Since the formal opening of the Border Crossing Inspection Posts (Pos Pemeriksaan Lintas Batas-PPLB) in Entikong West Kalimantan and Tebedu Sarawak, mobility of people and goods between West Kalimantan and Sarawak has increased significantly. This paper discusses the nature of mobility of goods and people between the two neighboring regions. Mobility of cars and labour is also discussed since mobility of cars affects mobility of people and goods while mobility of labour is an important part of mobility of people. The data show that the number of goods and people, which are out from the Entikong Post, is always greater than the number of goods and people, which enters to the Entikong Post. It is finally predicted, that economic benefits gained by West Kalimantan due to the Entikong Post, will be difficult to sustain in the future era of free trade. Especially if the government at the border districts does not enhance the capability of people to compete with foreign labour as well as foreign products.